Numerical simulation of proppant transport in a planar fracture. A study of perforation placement and injection strategy. (December 2018) - Baldini, Mauro; Carlevaro, C. Manuel; Pugnaloni, Luis A.; Sánchez, Martín
Highlights: CFD-DEM simulations of proppant transport are carried out for a scaled fracture. Different injection placement along the height of the fracture are considered. Different strategies for injecting different density proppants were studied. Mixing entropy is used to assess segregation on final deposited proppant dunes. Graphical abstract: Abstract: We present numerical simulations, based on a CFD–DEM approach, of the transport and settlement of proppant in a planar vertical cell that mimics a hydraulic fracture. These simulations, with resolution at the particle level, allow for a clean measurement of the dune placement and proppant degree of mixing. The effect of the position of the injection points is considered by three different injection heights in the vertical cell. Different proppant injection strategies were also considered by using two different proppant types that can be injected in different orders or simultaneously as a mixture. We evaluate the position and shape of the settled dune. We measure the degree of mixing of the two proppant types by using the concept of mixing entropy. We have found that an injection point placed close to the bottom of the cell leads to a dune close to the injection points, and that an injection point at the middle or at the top of the cell leads to a rather flat dune. Injecting different proppant types in different orders yields distinctive proppant distributions. This helps in evaluating the benefits of positioning perforation clusters close to geological boundaries that favor fracture growth in the upward or downward direction as well as selecting the order of proppant mesh injection. All the simulations correspond to the early stage, before the "traction carpet" effect comes into play.